Patients’ experiences and perspectives of patient-reported outcome measures in clinical care: A systematic review and qualitative meta-synthesis - Liam Carfora; Ciara M. Foley; Phillip Hagi-Diakou; Phillip J. Lesty; Marianne L. Sandstrom; Imogen Ramsey; Saravana Kumar (PLoS ONE, 2022)
Background Patient-reported outcome measures (PROMs) or patient-reported outcomes (PROs) are used by clinicians in everyday clinical practice to assess patients’ perceptions of their own health and the healthcare they receive. By providing insight into how illness and interventions impact on patients’ lives, they can help to bridge the gap between clinicians’ expectations and what matters most to the patient. Given increasing focus on patient-centred care, the objective of this meta-synthesis was to summarise the qualitative evidence regarding patients’ perspectives and experiences of the use of PROMs in clinical care. Methods A systematic search of the following databases was undertaken in August 2020: Medline, EMBASE, EMCARE, PsychINFO, Scopus and the Cochrane Library. This review was conducted and reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Methodological quality of the included studies was assessed using the Critical Appraisal Skills Programme checklist for qualitative research (CASP). A meta-ethnographic approach was used for data extraction and meta-synthesis of findings (PROSPERO registration: CRD42020202506). Results Fourteen studies from a range of countries with differing qualitative research methodologies were identified. Three themes were identified, namely ‘patient preferences regarding PROMs’, ‘patient perceived benefits’ and ‘barriers to patient engagement with PROMs’. The perspectives of patients suggested they preferred PROMs that were simple and relevant to their conditions and found benefits in the way they facilitated self-reflection and effective communication with their clinicians. Patients, however, questioned the relevance of some individual questions and purpose. Conclusion PROMs can be a useful tool in the clinical setting by enabling individualisation and patient centred care. This meta-synthesis provides insights into what patients find beneficial as well as barriers to their engagement, highlighting the importance of educating patients about PROMs.